Growth of Eggplant in Early Generative Stage to Application of Ameliorants and Mycorrhizal Biofertilizer During Water Saturated Stress (International Forum of Researchers and Lecturers, 2024)
Eggplant cultivation can be done in various types of land, because eggplant is a plant that is easy to adapt to the soil environment. One of the lands that can be used for eggplant cultivation is lebak swamp land by applying ameliorants and mycorrhizal biofertilizers. The purpose of the study was to determine the growth response and high level of resistance of purple eggplant plants by giving a combination application of ameliorants and mycorrhizal biofertilizers in several water-saturated conditions in the early generative phase. The research was conducted in the Laboratory and Experimental Garden of the Agrotechnology Study Program, Faculty of Plant and Animal Sciences, Bina Insan University, from July to November 2024. The research design used was a Factorial Completely Randomized Design (CRD) with two treatment factors, the first factor was water saturation conditions (S) and the second factor was the combination of ameliorants and mycorrhizal biofertilizers (M). The results showed that the treatment of water saturation conditions had a significant effect on plant height, stem diameter, number of leaves, root length and dry weight of eggplant plants, while the treatment of ameliorants and mycorrhizal biofertilizers only had a significant effect on the number of leaves. Water saturation conditions and the combination of ameliorants and mycorrhizal biofertilizers showed very significantly different interaction results only on plant height and number of leaves.